Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Perempuan terhadap Deteksi Dini Kanker Serviks dengan Pemeriksaan IVA atau Pap Smear - Fathimah Kalimasada Qaulitstsabit; Tutik Rahayu; Sri Wahyuni (Jurnal Ventilator, 2025)
Globally, cervical cancer was the fourth most common cancer among women, with low screening coverage contributing to the high number of cases diagnosed at an advanced stage. This study aimed to identify the factors influencing women's compliance with cervical cancer screening through IVA or Pap smear examinations. The research employed a quantitative method with a cross-sectional design. The study sample consisted of 112 respondents, selected using a simple random sampling technique. Data were analyzed using descriptive frequency tests, chi-square tests, and multiple logistic regression analysis.The results showed a significant relationship between several factors and women's compliance with early cervical cancer detection, including age (p=0.000), occupation (p=0.002), the number of children born (parity) (p=0.000), general health condition (p=0.018), distance to healthcare facilities (p=0.006), level of knowledge (p=0.021), family support (p=0.011), and the role of healthcare workers (p=0.000). However, education (p=0.104) did not show a significant relationship. Based on the multiple logistic regression analysis, the most influential factor affecting women's compliance with early cervical cancer detection was age (p=0.045).